2004
DOI: 10.2116/analsci.20.1399
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Aided Determination of Iodate and Bromate in Drinking Water by Microcolumn Ion Chromatography with Precolumn Enrichment

Abstract: Ozonization has recently replaced the chlorination of many types of water, since ozone is effective for disinfection. However, since ozone is a very strong oxidant, bromide (Br -) contained in water is also oxidized to form hypobromous acid (HOBr) or hypobromite (OBr -). The latter reacts with excess ozone to form bromate (BrO3 -), which is a disinfection byproduct. 1 The toxicity of BrO3 -has been studied, revealing that BrO3 -is carcinogenic to animals.2 Therefore, the maximum contaminant level of BrO3 -has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Macrocyclic compounds such as crown ethers, cryptands, cyclodextrins and resorcinarenes have been introduced as effective IC exchangers in both stationary and mobile phases. [22][23][24][25][26] The resorcinarenes are a recently developed class of macrocyclic compounds used as ion exchangers and our previous research on resorcinarene stationary phases confirms their usefulness as separators in IC systems. 25,[27][28][29][30] Synthesizing these compounds with long alkyl chains facilitates their adherence to the packing resin.…”
Section: Introductionmentioning
confidence: 83%
“…Macrocyclic compounds such as crown ethers, cryptands, cyclodextrins and resorcinarenes have been introduced as effective IC exchangers in both stationary and mobile phases. [22][23][24][25][26] The resorcinarenes are a recently developed class of macrocyclic compounds used as ion exchangers and our previous research on resorcinarene stationary phases confirms their usefulness as separators in IC systems. 25,[27][28][29][30] Synthesizing these compounds with long alkyl chains facilitates their adherence to the packing resin.…”
Section: Introductionmentioning
confidence: 83%
“…Although many papers have focused on the detection of iodate and perchlorate in water (Charles and Pepin, 1998;Handy et al, 2000;Kitamaki and Takeuchi, 2004;Krynitsky et al, 2004;Li and George, 2005;Winkler et al, 2004b), few have reported their occurrence in bottled water. This chapter presents a review of the occurrence of iodate and perchlorate in bottled water.…”
Section: Perchlorate and Iodate In Watermentioning
confidence: 99%
“…At present, the commonly applied method for bromate determination is ion chromatography combined with different detection modes including conductivity detection (IC-CD) (Lawal et al 2010;Michalski 2005), post-column reaction (IC-PCR) and ultraviolet (UV) detection (de Borba et al 2005;Kitamaki and Takeuchi 2004), or mass spectrometry detection (IC-MS) (Barron and Paull 2006;Eickhorst and Seubert 2004). Besides, other methods such as flow injection analysis, high-performance liquid chromatography (HPLC), gas chromatography (GC), and capillary electrophoresis (CE) are also applied for the purpose.…”
Section: Introductionmentioning
confidence: 99%